Papua New Guinea : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper analyzes the sustainability of Papua New Guinea's current and medium-term fiscal policy and its consistency with government objectives. The Papua New Guinea government faces major challenges in shaping a fiscal policy that promotes stability, meets development needs, and adheres to its debt ceilings over the medium term. It could decide to continue with its current fiscal stance, which would see its resource wealth exhausted quickly through large development spending. This approach would likely require continued borrowing and leave little savings for future generations.